1999
DOI: 10.1097/00005768-199901000-00006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of progressive resistance training on bone density: a review

Abstract: Osteoporosis is a major public health problem that is characterized by low bone mass and increased susceptibility to fractures, primarily of the hip, spine, and wrist. It is estimated to cause 1.5 million fractures annually in the United States in people aged 50 yr and older. Physical activity, particularly weight-bearing exercise, is thought to provide the mechanical stimuli or "loading" important for the maintenance and improvement of bone health, whereas physical inactivity has been implicated in bone loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
141
0
8

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(151 citation statements)
references
References 33 publications
2
141
0
8
Order By: Relevance
“…(1) Bone modeling, which occurs during development and is induced in adults by mechanical loading (2) or injury, (3) proceeds via uncoupled anabolic osteoblast bone formation and/or catabolic osteoclast bone resorption at distinct anatomic locations. (4) In contrast, bone remodeling is achieved through quantitatively coupled sequential events of osteoclastic bone resorption and osteoblastic bone formation within the spatial confines of basic multicellular units (BMUs).…”
Section: Introductionmentioning
confidence: 99%
“…(1) Bone modeling, which occurs during development and is induced in adults by mechanical loading (2) or injury, (3) proceeds via uncoupled anabolic osteoblast bone formation and/or catabolic osteoclast bone resorption at distinct anatomic locations. (4) In contrast, bone remodeling is achieved through quantitatively coupled sequential events of osteoclastic bone resorption and osteoblastic bone formation within the spatial confines of basic multicellular units (BMUs).…”
Section: Introductionmentioning
confidence: 99%
“…5 Currently, resistance exercise (RE) is recommended as a complement to an aerobic training programme 2,6 and offers many benefits for the aging population, including the prevention and treatment of osteoporosis and sarcopaenia. [7][8][9] A meta-analysis reported that dynamic resistance training reduced SBP and DBP of 4.6 and 3.8 mm Hg, respectively, 10 in normotensive adults, but the haemodynamic effects of dynamic resistance training have not been studied in a hypertensive population. Confounding the recommendation employing RE as an exercise regimen, recent evidence indicates that RE may cause increased arterial stiffness in young, healthy normotensive individuals.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 After the analysis of strength exercise in controls, low, and high intensities for 1 year, the high-intensity exercise group showed improvement in BMD. 25 It was reported that endurance running exercise was also helpful to BMD. 24 However, some studies reported no significant improvement.…”
Section: Discussionmentioning
confidence: 99%